E-Filing vs Non E-Filing: Taxpayers Perceptions of Use-fulness, Ease, Security, Confidentiality, and Satisfaction - Pramesti, Ria Adhi; Sukirman, Sukirman; Bawono, Icuk Rangga (Universitas Syiah Kuala, 2020)
Objective Tax reporting through the Annual Tax Return (SPT) is one of the obligations of taxpayers as mandated by the Indonesian Taxation Law. Along with the development of science and technology, technological innovation has been adopted as a form of internet-based taxation service called the e-filing system. This study is aimed to compare the perceived usefulness, convenience, security and satisfaction of taxpayers between users of e-filing and non e-filing. Design/methodology Primary and secondary data are collected through survey method in Tax Office (KPP) Pratama Purwokerto, Central Java Province, Indonesia. The registered taxpayers using e-filing are 17,831 and the non e-filing are 44,332. Paired t-test was used to compare each variable between users of e-filing and non e-filing.Results The findings reveal that there is no difference in perceived usefulness between the users of e-filing and non e-filing in that reporting tax return online and manual are equally perceived useful. Nevertheless there is a difference in the perceived convenience and security whereby users perceived that the use of e-filing is more convenient, secure and confidential than the manual. Furthermore there is no difference in the perceived satisfaction whereby users are equally satisfied either with the e-filing and non e-filing. As a whole, there are differences of perception between users of e-filing and non e-filing, hence it can be concluded that the benefits of the usefulness of e-filing is influenced by variables of usability, convenience, security, confidentiality and satisfaction of taxpayers on e-filing.